Efektivitas Duta Genre dalam Memasyarakatkan Program Genre BKKBN di Kota Padang - Yatsuko Juliana Sukamto; Hasbullah Malau (Journal of Education on Social Science (JESS), 2019)
This article aims to determine the effectiveness, constraints faced by Duta Genre in socialize Genre Program BKKBN in Padang City. As well as knowing how far the role of government overcome the genre ambassador problem in socialize genre BKKBN program. This research uses a qualitative approach which is interpreted as a research resulting in a descriptive form of words that can be observed and directed to the background individually and in society. A qualitative research approach is a complex, in-depth approach. The informant is derived from the management of the generation planning Program, including Kasubid area of population control, counseling and mobilization DP3AP2KB Kota Padang, and from the Genre ambassadors. Based on the results of the study, the genre ambassadors in socialize BKKBN program in Padang City can be said to be effective. Padang City people feel the benefits of the presence of the genre ambassadors in socialize Genre BKKBN program. The changes that occurred after the ambassador genre can also be seen from the problem of young marriage, Napza, free sex, and readiness of human resources who are ready to receive the BKKBN program through the genre ambassadors by proving the public can Overcome obstacles. But there is still a shortage in the implementation of the genre ambassador activities in socialize Genre BKKBN program is weak supervision done to the event of the ambassador of the genre itself.